Relationship between ectopic calcifications and bone fragility depicted on computed tomography scan in 70 patients with systemic sclerosis. Issue 3 (October 2022) - Fauny, Marine; Bauer, Elodie; Allado, Edem; Albuisson, Eliane; Deibener, Joëlle; Chabot, François; Mandry, Damien; Huttin, Olivier; Chary-Valckenaere, Isabelle; Loeuille, Damien
Background: A higher risk of osteoporotic fracture was described in systemic sclerosis patients than in healthy patients. Objective: To evaluate the relation between osteoporotic fracture risk measured by the scanographic bone attenuation coefficient of the first lumbar vertebra (SBAC-L1) on computed tomography (CT) scan and the presence of ectopic calcifications: vascular, valvular and spinal. Methods: This monocentric retrospective study was performed on patients followed between 2000 and 2014 at Nancy University Hospital. Systemic sclerosis patients, according to ACR/EULAR 2013 criteria, followed from 2000 to 2014 and who underwent, during their follow-up, a CT including the first lumbar vertebra were included. The SBAC-L1 was measured with a threshold set at 145 Hounsfield units (HU). Vascular and spinal calcifications were studied on CT. For vascular calcifications, the Agatston score was used. Valvular calcifications were studied on echocardiography. Results: A total of 70 patients were included (mean age: 62.3 (±15.6) years, women 88.5%). The mean SBAC-L1 was 157.26 (±52.1) HU, and 35 patients (50%) presented an SBAC-L1 ⩽ 145 HU. The reproducibility of the calcification evaluation was good, with kappa coefficients varying between 0.63 and 1. In univariate analysis, spinal and vascular calcifications were associated with an SBAC-L1 ⩽ 145 HU, with ORs of 13.6 (1.6–113.3) and 8 (95%CI: 2.5–25.5), respectively. In multivariate analysis, the SBAC-L1 was not associated with the presence of any ectopic calcifications. The SBAC-L1 decreased with age (p = 0.0001). Conclusion: Patients with systemic sclerosis with an SBAC-L1 ⩽ 145 HU were older, but they did not have more ectopic calcification. Trial registration: The ethics committee of Nancy Hospital agreed with this study (referral file number 166). This study was designed in accordance with the general ethical principles outlined in the Declaration of Helsinki.